Effectiveness of Use of Single Dose Preoperative Antibiotic versus both Pre and Post Operative Antibiotics in Patients Undergoing Laparoscopic Uncomplicated Appendectomy in Birat Medical College Teaching Hospital (BMCTH) - Shrestha, Bhupendra Charan; Sharma, Shivraj; Yadav, Rohit Prasad; Agrawal, Chandra Shekar; Pandit, Narendra (Birat Journal of Health Sciences, 2022)
Introduction: Acute appendicitis is one of the most common surgical emergency. Rationalized use of antibiotics prevents the risk of post operative complications. There is no conclusive recommendation on the duration of antibiotic usage and role of postoperative use of antibiotics in preventing complications in uncomplicated cases remains controversial till date.Objectives: To compare the effectiveness of single dose preoperative antibiotic with preoperative and postoperative antibiotics for patients undergoing laparoscopic uncomplicated appendectomy.Methodology: A total number of 113 patients who fulfilled the selection criteria underwent laparoscopic appendectomy for uncomplicated appendicitis and were randomly divided into two groups. Group A patients received only pre operative antibiotics whereas Group B patients received both preoperative and postoperative antibiotics. Patients of both the groups were followed up postoperatively till discharge from the hospitalResults: In this study, patients who received only pre-operative antibiotic were 57 (50.4%) and patients who received both preoperative and postoperative antibiotics were 56(49.6%). SSI was detected in total of 2 patients (1.8%) one from each group and postoperative lump noted in right iliac fossa (RIF) in 2 patients (1.8%) one in each group intraoperatively in which further antibiotic was continued postoperatively. Hematoma, seroma and peritonitis were absent in both the groups. The difference between the two groups for incidence of SSI and postoperative RIF lump was statistically insignificant with P value of 0.748.Conclusion: Single dose preoperative antibiotic is sufficient in preventing postoperative complications in patients undergoing laparoscopic appendectomy for uncomplicated appendicitis. This can be recommended for implementation as standard operating protocol in such cases.